Cutting Edge: Overlapping Functions of TLR7 and TLR9 for Innate Defense against a Herpesvirus Infection - Zucchini, Nicolas; Bessou, Gilles; Traub, Stephanie; Robbins, Scott H; Uematsu, Satoshi; Akira, Shizuo; Alexopoulou, Lena; Dalod, Marc (The Journal of immunology (1950), 2008)
As initially demonstrated with murine cytomegalovirus (MCMV), plasmacytoid dendritic cells (pDCs) are the major source of IFN-α/β in response to a variety of viruses in vivo. However, contradictory results have been obtained pertaining to the mechanisms promoting IFN-α/β production by pDCs in response to MCMV. In this study we show that TLR7 and TLR9 exert redundant functions for IFN-α/β, IL-12p40, and TNF-α production by pDCs in vivo during MCMV infection. In contrast, we confirm that systemic production of IL-12p70 strictly depends on TLR9. The combined loss of TLR7 and TLR9 recapitulates critical features of the phenotype of MyD88-deficient mice, including a dramatic decrease in systemic IFN-α/β levels, an increase in viral load, and increased susceptibility to MCMV-induced mortality. This is the first demonstration of the implication of TLR7 in the recognition of a DNA virus.